Mercuric Ion Sensing by an Overlapping β‐turn Containing Peptide. Issue 26 (18th September 2017) - Tomar, Kalpana; Soni, Satyendra; Bhadauriya, Pratibha; Parihar, Rashmi; Ganesh, Subramaniam; Nair, Nisanth N.; Ramanathan, Gurunath
Abstract: A tetrapeptide containing dehydrophenylalanine residue exhibits unusual enhanced fluorescence emission intensity for Hg 2+ ions selectively. In vivo studies on HeLa cells revealed that this peptide could be used to study Hg 2+ trafficking in mammalian cells. The results demonstrate that Hg 2+ can interact with sulfurless peptide backbones, if the latter provides the requisite geometry, especially a folded type III/III overlapping beta turn conformation. Abstract : An overlapping beta turn containing peptide devoid of any sulfur or selenium but containing an N, N ‐diphenylamino group at the para position of a dehdrophenylalanine residue could be used for imaging mercuric ions in vivo .